THE ROLE OF ORGANIZATIONAL EXPERIENCE IN GROWING LEADERSHIP MINDSET AND CAPABILITY - Muhammad Syarofi ofy; Ghoni Rizky Ridho Illah; Dian Lestari (Airlangga Journal of Innovation Management, 2022)
The organization is a place that can provide good leadership benefits related to a growth mindset and capability of communication or socialization. High socialization skills can be formed when someone joins the organization. This discussion focuses on the formation of perspectives or benefits obtained after joining an organization. This purpose is to inform that by following an organization, one can grow personal thinking to have leadership qualities and, with the existing experience, can hone ourselves. This discussion uses a qualitative descriptive method by collecting data on the problems discussed from sources from a literature review, explaining each study point discussed. The result of this discussion is that the organization can provide benefits that can foster a person's mindset to be better in shaping the spirit of leadership. Organizations can provide a different way of thinking, such as forming good relationships between individuals and groups and fostering a leadership spirit. This is in accordance with what was obtained during the process of organizing. During joining the organization, the benefits are obtained through the attitudes and traits that must be applied. This research found that organizational experiences is important to build a mindset, communication skill, and leadership capabilities that are beneficial for human social lives.